Effect of Ultrasound-Guided Versus Conventional Recruitment Manoeuvres on Lung Aeration in Morbidly Obese Patients Undergoing Laparoscopic Bariatric Surgery: A Randomised Controlled Trial - Omar Mohamed Fathey Elkady; Sameh Abdelkhalik Ahmed; Mohamed Mohei Abu Yazed; Abdelraheem Moustafa Dowidar; Aliaa Mohamed Belal (Bali Journal of Anesthesiology, 2025)
Background: Morbidly obese patients are at increased risk for intraoperative atelectasis and postoperative pulmonary complications (PPCs), especially during laparoscopic surgery. Lung recruitment manoeuvres (RMs) are used to reverse atelectasis, and lung ultrasonography may offer a real-time, individualised approach to guide these interventions. This study aimed to compare the efficacy of ultrasound-guided versus conventional RMs on lung aeration and oxygenation in patients undergoing laparoscopic bariatric surgery. Materials and Methods: In this prospective, double-blind randomised controlled trial, 60 morbidly obese adult patients (BMI >40 kg/m²) scheduled for elective laparoscopic bariatric surgery were randomly assigned to either an ultrasound-guided recruitment group (Group US) or a conventional recruitment group (Group C). The primary outcome was the change in lung ultrasound score (LUS) from post-induction (T1) to the end of surgery (T3). Secondary outcomes included LUS at all time points (T1–T4), dynamic lung compliance, modified airway driving pressure, intraoperative and postoperative oxygen desaturation, and the incidence of PPCs within 48 h. Results: Both groups showed significant improvement in LUS by the end of surgery, but the reduction was greater in Group US [median change: −2 (IQR: −2 to −2)] compared to Group C [−1 (IQR: −2 to −1); P < 0.001]. Oxygen saturation improved significantly in Group US after the second recruitment (P = 0.04), although other respiratory parameters, desaturation events, and PPC rates did not differ significantly between groups. Conclusion: Ultrasound-guided RMs significantly improved lung aeration in morbidly obese patients undergoing laparoscopic bariatric surgery compared to conventional manoeuvres, without adverse haemodynamic or respiratory effects.